Inclusive Education Management in Supporting the Potential of Children with Disabilities to Achieve at the Junior High School in Indonesia - Astuti, Vera; Subandi; Romlah, Romlah (Ahlussunnah: Journal of Islamic Education, 2025)
This study aims to analyze inclusive education management in developing the potential of gifted children with disabilities at Bandar Lampung Junior High School 14. The research method used is a qualitative approach with a case study type, through data collection techniques in the form of observation, in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that POAC-based inclusive management (Planning, Organizing, Implementing, and Evaluating) has been systematically implemented. At the planning stage, the school conducted a needs assessment, developed an Individual Learning Program (PPI), and modified the curriculum according to the students' conditions. The organization of services involved the principal, teachers, special guidance counselors, parents, and external experts to ensure effective coordination. The implementation of learning uses differentiation strategies, multisensory media, and individual assistance, and is supported by extracurricular activities for talent development. Evaluation is carried out continuously through academic assessment and individual development assessment. This study concludes that inclusive education management has a significant impact on the academic, social, emotional, and non-academic development of students with disabilities, despite obstacles such as limited resources and the need for teacher training.